Strategic Demand Response for Economic Dispatch in Wind-Integrated Multi-Area Energy Systems - Peng Li; Li Wang; Peiqiang Zhang; Peng Yan; Chongyang Li; Zhe Nan; Jun Wang (Energies)
The rapid integration of renewable energy sources and the increasing complexity of energy demands necessitate advanced strategies for optimizing multi-region energy systems. This study investigates the coordinated energy management of interconnected parks by incorporating wind power, demand response (DR) mechanisms, and energy storage systems. A comprehensive optimization framework is developed to enhance energy sharing among parks, leveraging demand-side flexibility and renewable energy integration. Simulation results demonstrate that the proposed approach significantly improves system efficiency by balancing supply-demand mismatches and reducing reliance on external power sources. Compared to conventional methods, the DR capabilities of industrial and commercial loads have increased by 8.08% and 6.69%, respectively, which is primarily due to enhanced utilization of wind power and optimized storage deployment. The inclusion of DR contributed to improved system flexibility, enabling a more resilient energy exchange framework. This study highlights the potential of collaborative energy management in multi-area systems and provides a pathway for future research to explore advanced control algorithms and the integration of additional renewable energy sources.